Ijtihad Istinbati dan Tatbiqi - Syabbul Bachri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to examine the concept of ijtihad istinbati and ijtihad tatbiqi in the context of Islamic law development that is adaptive to social reality. Ijtihad istinbati focuses on determining the law based on shar'i principles, while ijtihad tatbiqi emphasizes the application of the law in the actual context. This study uses a qualitative method with a literature review approach, examining classical and contemporary works of ushul fiqh that discuss the dynamics of ijtihad. The results show that the integration of the two types of ijtihad is very important in answering modern legal issues. Ijtihad istinbati provides a normative foundation, while ijtihad tatbiqi guarantees the relevance of the law to changing social conditions. This study emphasizes that the balance between text and context is key in developing Islamic law that is responsive and solution-oriented to the challenges of the times.